Acute Kidney Injury Due to Interaction of Methyl-1-testosterone with Ciclosporin Metabolism in a Patient with Severe Atopic Dermatitis - Al-Niaimi, Firas (Springer Healthcare, 2013)
Ciclosporin is widely used in a number of inflammatory disorders and has the potential for drug interactions. We report here a case of acute kidney injury due to the interaction of ciclosporin with methyl-1-testosterone. This has not been previously reported and it is relevant as methyl-1-testosterone can be purchased online. Physicians should be aware of any over the counter or online purchased “supplements” and consider possible drug interactions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13555-013-0038-6) contains supplementary material, which is available to authorized users.